2016
DOI: 10.1038/srep26476
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for Gene Expression Studies related to lung injury in a preterm lamb model

Abstract: Preterm newborns often require invasive support, however even brief periods of supported ventilation applied inappropriately to the lung can cause injury. Real-time quantitative reverse transcriptase-PCR (qPCR) has been extensively employed in studies of ventilation-induced lung injury with the reference gene 18S ribosomal RNA (18S RNA) most commonly employed as the internal control reference gene. Whilst the results of these studies depend on the stability of the reference gene employed, the use of 18S RNA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…Finally, the different results obtained for TNFα expression levels between groups (resistant and susceptible to H. contortus infection) depending on the reference gene used have demonstrated that inappropriate reference gene selection can lead to misinterpretation of gene expression results. This fact is due to high expression variations in a non-stable reference gene being transferred to the target-gene, which can lead to under-or over-estimation of the relative quantification data and important changes in statistical significance, corroborating the findings of other studies [20,33,34,45].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, the different results obtained for TNFα expression levels between groups (resistant and susceptible to H. contortus infection) depending on the reference gene used have demonstrated that inappropriate reference gene selection can lead to misinterpretation of gene expression results. This fact is due to high expression variations in a non-stable reference gene being transferred to the target-gene, which can lead to under-or over-estimation of the relative quantification data and important changes in statistical significance, corroborating the findings of other studies [20,33,34,45].…”
Section: Discussionsupporting
confidence: 83%
“…Selection of the reference gene candidates was based on those commonly used for RT-qPCR studies in different ruminant tissues [30][31][32][33][34]. Five reference gene candidates with different cellular functions were selected: glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and glucose 6-phosphate dehydrogenase (G6PDH), enzymes associated with carbohydrate metabolism; tyrosine 3-monoxygenase (YWHAZ), involved in intercellular signal transduction; actin beta (ACTB), cytoskeletal structural protein; beta-2 microglobulin (B2M), a component of histocompatibility complex (MHC) class I beta chain.…”
Section: Reference Genes and Target Gene Selectionmentioning
confidence: 99%
“…Thus, it is advisable to evaluate reference genes by more than one method and integrate the data to generate final ranking, especially in tissues like liver. Here, we calculated the comprehensive ranking by geometric mean of results by all the software programs324041. And validation by Leptin and Ppar-γ expression assessment confirmed the reliability of this strategy.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, the least stable genes were Gapdh > Hmbs > Pgk1 showed by geNorm, Gapdh > Hmbs > Rpl13a by NormFinder and Gapdh > Pgk1 > Hmbs by BestKeeper (Table 3). While reference genes ranking varied slightly by algorithm, the overall ranking of the best candidate reference genes were calculated through geometric means of the three ranking numbers and the most stable reference genes had the smallest geometric mean324041 (Table 3). The comprehensive ranking showed that β2m and Hprt appear to be the most suitable reference gene pair in iWAT of CR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation